2013
DOI: 10.3319/tao.2013.07.04.01(t)
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Coupling Between Meteorological Parameters and Secondary Microseisms

Abstract: The basic scientific question of this study was: do other mechanisms exist for excitation of secondary microseisms aside from the widely accepted mechanism by non-linear interactions of respective ocean waves. Here we use continuous broadband data from secondary microseisms recorded at the Ostrava-Krásné Pole, Czech Republic (OKC) seismic station to create a massive seismological database. Except for seismological data, various meteorological features and their mutual relations were analysed: temperature, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…It can be stated that the excitation of secondary microseisms due to windstorms above the ocean is not the necessary condition for their excitation but represents only a triggering mechanism. Similarly, the third triggering mechanism connected with deformation waves after catastrophic earthquakes shows the same background as this process, i.e., excitation of secondary microseisms after catastrophic earthquakes in summer is relatively low, but the generation of secondary microseisms in winter is likely higher, even for less intensive earthquakes from the group of catastrophic ones Holub et al 2013).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…It can be stated that the excitation of secondary microseisms due to windstorms above the ocean is not the necessary condition for their excitation but represents only a triggering mechanism. Similarly, the third triggering mechanism connected with deformation waves after catastrophic earthquakes shows the same background as this process, i.e., excitation of secondary microseisms after catastrophic earthquakes in summer is relatively low, but the generation of secondary microseisms in winter is likely higher, even for less intensive earthquakes from the group of catastrophic ones Holub et al 2013).…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown that most microseisms anomalies are connected with atmospherics or strong earthquakes (Holub et al 2013). But, in fact, these influences were only triggers for the anomalous microseisms and not the reason of higher microseisms during winter.…”
Section: The Analysis Of the Basis For The Annual Variations Of Micromentioning
confidence: 99%
See 3 more Smart Citations